No improvement in injection frequency or in visual outcome over time in two cohorts of patients from the same Swedish county treated for wet age-related macular degeneration - Schroeder M; Rung L; Lövestam-Adrian M (Clinical Ophthalmology, 2017)
Marion Schroeder,1 Lena Rung,2 Monica Lövestam-Adrian1 1Division of Ophthalmology, Department of Clinical Sciences Lund, Lund University, Skåne University Hospital, Lund, 2Department of Ophthalmology, Helsingborg Hospital, Helsingborg, Sweden Background: Although ranibizumab has been used for the treatment of wet age-related macular degeneration (AMD) since 2007, real-world studies still report undertreatment resulting in a less favorable visual outcome. In this study, two different time cohorts of patients treated with ranibizumab for wet AMD in routine care were analyzed to observe whether there was a change over time regarding visual outcome, injection frequency, and quality of life (QoL). Methods: We compared patients with treatment-naïve wet AMD in two observational follow-up cohorts 2007–2010 (n=50 patients) and 2009–2013 (n=26). After a loading dose of three intravitreal ranibizumab injections, the patients were treated under the pro re nata regimen. Visual acuity (VA) was examined by Early Treatment Diabetic Retinopathy Study (ETDRS) charts. The National Eye Institute Visual Functioning Questionnaire 25 was answered by patients at baseline and at 37±7 months (cohort 1) and at 45±4 months (cohort 2). Results: At baseline, the cohorts were homogeneous considering mean age (76±7 vs 75±8 years), mean VA (53±14 vs 52±15 ETDRS letters), and mean self-reported symptom duration (14±11 vs 13±11 weeks). Mean VA decreased in both cohorts over time, from 53±14 to 45±24 letters (P=0.011) and from 52±15 to 46±22 letters (P=0.175), respectively. The patients received a mean of 8±5 and 9±7 injections, respectively. The mean composite score change from baseline to follow-up decreased in cohort 1 from 64±21 to 59±25 scores (P=0.04) but increased in cohort 2 from 64±28 to 67±23 scores (P=0.38). Conclusion: We could not demonstrate any improvement in the number of injections in two different time cohorts of patients treated with ranibizumab for wet AMD in a Swedish county. Visual outcomes decreased after 3 years of follow-up, but QoL scores were divergent. Keywords: neovascular AMD, anti-VEGF, NEI VFQ-25, clinical care